Folia de Reis como patrimônio cultural em Itapuranga-GO : compartilhamento de saberes, memórias e significados - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This work aimed to analyze the current scenario of “Folias de Reis” in the city of Itapuranga-GO, in order to examine the relevance of memory, identity and cultural heritage from the perspective of preserving this celebration. The investigation followed a qualitative approach of a bibliographic nature, through a survey of the conceptualization of memory and identity based on the reflections of Joel Candau (2021), Pierre Nora (2012) and Ecléa Bosi (1994). These authors emphasize that if we remember it is because others and the present situation remind us. With a view to educational actions that would enable the recording, interaction and visibility of knowledge arising from the knowledge, practices and experiences of living individuals through memory, through a Heritage Education project, we sought to provide opportunities for students and teachers to have contact with experiences. This work also analyze the knowledge and forms of expression of the Folia de Reis cultural manifestation as Intangible Cultural Heritage. This cultural practice intertwines and expands knowledge of oneself and others, by promoting empathy, respect for culture, identities and differences between people, without prejudice of any kind. The results demonstrated that through the tradition of knowledge passed from generation to generation, Folia de Reis in the municipality of Itapuranga remains alive and is being remade in diverse spaces and places, in which men and women weave their stories of life and their community. Based on the research results, aiming to meet the didactic need for materials that address local history and cultural heritage, as well as contributing to the dissemination of the meanings and meanings of a manifestation of the Intangible Cultural Heritage of the municipality of Itapuranga, An educational book in E-book format was created as an educational product. This material, as a suggestion for teaching support, presents proposals that can be developed by the school community that meet the demands of both teachers and elementary school students.
Folia de Reis as cultural heritage in Itapuranga-GO : sharing knowledge, memories and meanings
Keywords: Folia de Reis; Memória; Identidade; Patrimônio cultural; Memory; Identity; Cultural heritage; CIENCIAS HUMANAS::HISTORIA